Quantification Methods of Pigments and its Potential As Biomarkers for Estimation of Phytoplankton Biomass - Qadar Hasani (Jurnal Biologi Tropis, 2023)
Pigments and chlorophyll are essential for the process of photosynthesis and are characteristic of each species of phytoplankton. This study aims to provide an overview of the pigment quantification method and its potential to identify and estimate biomass of phytoplankton. A literature review has been carried out to identify methods for the extraction and quantification of phytoplankton. The results of the study found that there are at least two main methods most commonly used for the extraction and quantification of phytoplankton, namely spectrophotometric analysis and HPLC. Spectrophotometric is considered a good and practical method for estimating chlorophyll. However, the HPLC has also become the main method for investigating the taxonomic composition of phytoplankton populations. The researchers concluded that there was no significant difference in results between two methods. Spectrophotometric analysis is much cheaper and faster than HPLC, make it a good tool for routine evaluation of chlorophyll. However, the use of HPLC has been proven to be the most appropriate for determining concentration of various pigments in the community of phytoplankton. Regardless of the various advantages and disadvantages of both methods, a good understanding of each method should be a concern in terms of selecting the method to be used according to its designation.